(3GdCMGOjK GdeNJGQIs - (3eMeO Hf YHO GdhGMO Hf CMeO Hf YHO GdQMef GdSYOj GdebOSj, VjGA GdOjf CHh YHO Gddg,J (B643 (3g` s
(3ChdgG (B:s
(3Yf GdfHi Udi Gddg Ydjg hSde Cfg deG ONd ecg hLO HgG KdGKeGFg hSJjf UfekG aCTGQ HYUGg Edi Ufe hbGd LGA GdMb hRgb GdHGWd Ef GdHGWd cGf RghbkG ajSbW jYfi GdVe hdGjeTg s
(3BNQgG (B:s
(3SeY gPG GdLRA Ydi LGeYg GdTjN CHh YHO Gddg eMeO Hf YHO GdhGMO GdebOSi s
(3GdfSNI HgG MhGTs
(3YdjgG SeGYGJ HBNQgGs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B263s
Keywords: (3GdMOjK h GdeUWdMs